2017
DOI: 10.1093/cid/cix506
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Cardiac DNA Methylation Fingerprint and Gene Expression Analysis Provide New Insights in the Pathogenesis of Chronic Chagas Disease Cardiomyopathy

Abstract: SummaryDNA methylation analysis on global gene expression in myocardial samples from patients with end-stage chronic Chagas cardiomyopathy leads to the identification of novel potential disease pathways and therapeutic targets linked to electrical conduction or immune response modulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 37 publications
8
42
0
Order By: Relevance
“…The confirmation rate was 86%, and only for 6 genes (ABRA, CDC42, ESRRA, GPD1, NFATC2, TGFBR2), the expression patterns were not confirmed. The gene specific qRT-PCR results, including fold change and p values, were previously described ([ 39 ], S2 Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The confirmation rate was 86%, and only for 6 genes (ABRA, CDC42, ESRRA, GPD1, NFATC2, TGFBR2), the expression patterns were not confirmed. The gene specific qRT-PCR results, including fold change and p values, were previously described ([ 39 ], S2 Table ).…”
Section: Resultsmentioning
confidence: 99%
“…More recently, whole blood transcriptional profiling has been used to study human host responses to protozoan pathogens such as malaria [20, 21] and Chagas disease caused by Trypanosoma cruzi [22, 23]. Expression profiling has also been applied in the context of animal models [2426] and in human studies [15, 2729] of the leishmaniases.…”
Section: Introductionmentioning
confidence: 99%
“…SMOC2 could be a potential significance factor that altered remodeling and inflammation for further study in the mechanism of HF. Laugier et al (2017) found that SMOC2 , involved in matrix remodeling, is potentially associated with the increased T-helper 1 cytokine-mediated inflammatory damage in heart, using genome-wide cardiac DNA methylation on global gene expression in myocardial samples in chronic Chagas disease cardiomyopathy, which is an inflammatory cardiomyopathy presenting with heart failure and arrhythmia.…”
Section: Resultsmentioning
confidence: 99%